The Redemption of the Disabled : a study of programmes of rehabilitation for the disabled of war and of industry - Harris, Garrard, 1876-1927 (New York, NY : D. Appleton & Company, 1919)
This book, by Garrard Harris, is about the rehabilitation programs available for disabled war veterans.
Introduction : Physical reconstruction -- Chapter I. Redemption of the disabled : a social obligation -- Chapter II. Human wastage under the pension system -- Chapter III. The nation's duty toward the individual -- Chapter IV. What the belligerent nations have undertaken -- Chapter V. The problem of re-education -- Chapter VI. Belgium, the pioneer in restoration work -- Chapter VII. Systematic development in France -- Chapter VIII. Evolution of the British system -- Chapter IX. Restoration work in the central empires -- Chapter X. The practical Canadian system -- Chapter XI. Australia, New Zealand, South Africa, and India -- Chapter XII. Italy and her special problems -- Chapter XIII. The problem comes to America -- Chapter XIV. The development of a national programme -- Chapter XV. Financial provision for the disabled soldier -- Chapter XVI. The Vocational Rehabilitation Act -- Chapter XVII. The process of restoration -- Chapter XVIII. The choice of an occupation -- Chapter XIX. The training adapted to individual needs -- Chapter XX. The problem of placement -- Chapter XXI. Opportunities for the retrained in the public service -- Chapter XXII. Records of individual success -- Chapter XXIII. The duty of the home community -- Chapter XXIV. A sustained public sentiment necessary -- Chapter XXV. The larger problem : salvaging the disabled of industry -- Chapter XXVI. The place of the states in the programme.
Title from resource description page (viewed March 16, 2016).
Includes index.
In English.
Keywords: Disabled veterans -- Rehabilitation; People with disabilities -- Rehabilitation